Herpes simplex keratitis in central India: Clinical types, treatment patterns, and outcome measures - Samrat Chatterjee; Deepshikha Agrawal; Mehvish Malik (Indian Journal of Ophthalmology)
Purpose: Report clinical subtypes, treatment details, outcome, and recurrences in herpes simplex keratitis (HSK). Design: Retrospective, observational study. Methods: The medical records of all patients diagnosed with HSK between July 2019 and December 2023 at a single center were reviewed. The primary outcome measure was the clinical type of HSK, while secondary outcomes were treatment, and its outcome, and recurrences. Results: In total, 223 patients (225 eyes) were diagnosed with HSK. The most common type was herpes simplex virus (HSV) stromal keratitis without ulceration (102 eyes, 45.3%), followed by epithelial keratitis (57 eyes, 25.3%), endothelial keratitis (41 eyes, 18.2%), and stromal keratitis with ulceration (25 eyes, 11.1%). More males presented with epithelial and endothelial keratitis, while more females presented with stromal keratitis with ulceration (P = 0.02). Following treatment, 95 (42.2%) eyes were lost to review, 126 (56.0%) were resolved, and four (1.8%) developed microbial keratitis. Posttreatment visual acuity was highest in stromal keratitis without ulceration and lowest in stromal keratitis with ulceration (P = 0.001). Twenty-seven (12.1%) patients experienced 35 episodes of HSK recurrence. HSV stromal keratitis without ulceration (20 patients, 57.1%) was the most common form of recurrence, followed by epithelial keratitis (seven patients, 20%), endothelial keratitis (five patients, 14.3%), and stromal keratitis with ulceration (three patients, 8.6%). Conclusion: HSV stromal keratitis without ulceration was the most common presentation. Posttreatment improvement in visual acuity was best in this particular type of HSK and worst in stromal keratitis with ulceration. Recurrent disease was present in a significant proportion of patients.